Detecting Non-Markovianity of Quantum Evolution via Spectra of Dynamical Maps - Dariusz Chruscinski; Chiara Macchiavello; Sabrina Maniscalco (AMER PHYSICAL SOC, 2022)
We provide an analysis on non-Markovian quantum evolution based on the spectral properties of dynamical maps. We introduce the dynamical analog of entanglement witness to detect non-Markovianity and we illustrate its behavior with several instructive examples. It is shown that for several important classes of dynamical maps the corresponding evolution of singular values and/or eigenvalues of the map provides a simple non-Markovianity witness.